2020
DOI: 10.1111/1471-0528.16389
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol for open myomectomy: a systematic review and meta‐analysis of randomised control trials

Abstract: Background Excessive blood loss is a significant risk of myomectomy with the potential need for hysterectomy.Objective To study the effectiveness of preoperative misoprostol compared with placebo at open myomectomy on intra-and postoperative outcomes.Search strategy PubMed, Cochrane, Scopus, MEDLINE and EMBASE.Selection criteria Randomised control studies of women undergoing open myomectomy for symptomatic fibroids who were given either misoprostol or placebo preoperatively. Data collection and analysisThe rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…A meta‐analysis evaluating misoprostol, oxytocin, vasopressin, tranexamic acid, epinephrine, or ascorbic acid among different types of myomectomy reported that misoprostol and ornipressin were the least effective drugs in shortening hospital stay 36 . In two meta‐analyses drawing data from randomized controlled trials, no relationship was found between the use of misoprostol and length of hospital stay in women who underwent myomectomy 5,23 . In the current study, no relationship was found between hospital stay and misoprostol use, consistent with the results in the literature.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A meta‐analysis evaluating misoprostol, oxytocin, vasopressin, tranexamic acid, epinephrine, or ascorbic acid among different types of myomectomy reported that misoprostol and ornipressin were the least effective drugs in shortening hospital stay 36 . In two meta‐analyses drawing data from randomized controlled trials, no relationship was found between the use of misoprostol and length of hospital stay in women who underwent myomectomy 5,23 . In the current study, no relationship was found between hospital stay and misoprostol use, consistent with the results in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…In other studies, similar beneficial results were reported for the amount of bleeding and Hb values in women using misoprostol 14,16–22 . In a meta‐analysis evaluating randomized controlled trials, preoperative use of misoprostol in open myomectomy was associated with less blood loss, less decrease in hemoglobin, and fewer cases needing blood transfusion 23 . In another meta‐analysis, vaginal misoprostol recipients were reported experience lower levels of blood loss and hemoglobin decrease 11 .…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Indeed, ordered but undelivered transfusions are a health security problem in our country [5]. The uterine tourniquet technique allows reduction of both intraoperative hemorrhage, and transfusion needs during abdominal myomectomies better than use of misoprostol [15][16][17][18], oxytocics [13], gonadotrophin releasing hormon (GnRH) agonists [10] and tranexamic acid [19][20][21]. The uterine tourniquet has also shown its superiority over bilateral primary ligation of hypogastric arteries, which is reserved for experienced surgeons [15].…”
Section: Discussionmentioning
confidence: 99%